Constitutional Protection of Indigenous Customary Rights in National Strategic Projects Kertajati Airport - Zurotul Afifah; Amanta Tiara Farahita; Sapta Pratiwi (Program Studi Hukum Tata Negara, 2025)
This article examines the legal protection of customary land rights within the implementation of national strategic projects, using Kertajati Airport as a case study. The study interrogates the disjunction between Indonesia’s positive legal framework, particularly the 1960 Basic Agrarian Law and related sectoral regulations, and their practical application at the local level. Employing a normative juridical approach combined with systematic document analysis, this research evaluates statutory provisions, policy instruments, and administrative practices that shape the recognition and enforcement of indigenous tenure rights. The findings reveal that legislative ambivalence, overlapping institutional authorities, and fragmented sectoral regulations significantly weaken the protection of customary rights. Such conditions generate legal uncertainty and facilitate land acquisition practices that marginalize indigenous communities, thereby intensifying tensions between national development priorities and constitutional principles of social justice. The Kertajati Airport case further illustrates how formal compliance with development procedures may coexist with substantive deficiencies in rights protection, particularly concerning meaningful participation, prior consultation, and equitable compensation mechanisms. To address these challenges, the article proposes a more inclusive legal protection model by integrating participatory approaches into development planning and strengthening the role of local regulations in recognizing customary communities. Harmonizing national policies with responsive regional bylaws is essential to ensure cultural sustainability and legal certainty for indigenous peoples. This study contributes to contemporary scholarship on development law by offering a context-sensitive framework for balancing strategic infrastructure development with constitutional commitments to human rights, social justice, and equitable land governance, aligning with broader comparative discussions in global legal studies.